2015
DOI: 10.1002/2014jb011707
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic relaxation following subduction earthquakes and its effects on afterslip determination

Abstract: Afterslip is commonly thought to be the controlling process in postseismic deformation immediately following a great megathrust earthquake and is usually inferred from geodetic observations using purely elastic models. However, observed motion reversal of the near-trench area right after the 2011 M w 9 Tohoku-oki earthquake demonstrates the dominance of viscoelastic relaxation of coseismically induced stresses. To understand the importance of incorporating viscoelasticity in afterslip determination, we employ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
5

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(162 citation statements)
references
References 40 publications
9
148
5
Order By: Relevance
“…For example, Ozawa et al (2012) argued that afterslip was the dominant mechanism; Diao et al (2014) and Han et al (2014) examined the combined effects of afterslip and viscoelastic relaxation; Hu et al (2014) explored the effect of poroelastic rebound; and several authors showed that viscoelastic relaxation plays an important role even in short-term deformation (Sun et al 2014;Sun and Wang 2015;Hu et al 2016a). The most important results from these studies are those obtained using seafloor geodetic observation (SGO) (Watanabe et al 2014;Tomita et al 2015).…”
Section: Open Accessmentioning
confidence: 99%
“…For example, Ozawa et al (2012) argued that afterslip was the dominant mechanism; Diao et al (2014) and Han et al (2014) examined the combined effects of afterslip and viscoelastic relaxation; Hu et al (2014) explored the effect of poroelastic rebound; and several authors showed that viscoelastic relaxation plays an important role even in short-term deformation (Sun et al 2014;Sun and Wang 2015;Hu et al 2016a). The most important results from these studies are those obtained using seafloor geodetic observation (SGO) (Watanabe et al 2014;Tomita et al 2015).…”
Section: Open Accessmentioning
confidence: 99%
“…In addition, to obtain unbiased results of the inversion analysis, we need to use (1) proper plate interface geometry, (2) proper crustmantle rheological structure, and also (3) a consistent coseismic slip distribution, which causes coseismic stress changes in the asthenosphere. Diao et al (2014) and Yamagiwa et al (2015) as well as the present study performed simultaneous inversion for coseismic and postseismic slip distributions with a standard crust-mantle rheological structure model to satisfy the second and third requirements, but Sun and Wang (2015) and Hu et al (2016) did not. In our common understanding, as mentioned above, afterslip is considered to occur in a deep brittle-ductile transition zone so as to release the stress concentrations caused at the tip of main rupture.…”
Section: Discussionmentioning
confidence: 85%
“…For example, the result of inversion analysis by Perfettini and Avouac (2014) shows a dominant zone of shallow afterslip extending over the main rupture area near the trench. Sun and Wang (2015) have suggested the existence of large shallow afterslip outside of the main rupture area. Yamagiwa Vol.…”
Section: Spatiotemporal Distribution Of Afterslipmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent great subduction zone earthquakes, such as the 2010 M w 8.8 Maule earthquake in Chile and the 2011 M w 9.0 Tohoku earthquake in Japan, have greatly sharpened our view of various aspects of earthquake physics, including foreshock activity and its influence on mainshock nucleation, depth-dependent earthquake source properties, and structural and rheological control on coseismic and postseismic slip (Ando and Imanishi, 2011;Meng et al, 2011;Lay et al, 2012;Moreno et al, 2012;Sun and Wang, 2015). In particular, changes in seismicity patterns have shed light on the spatiotemporal evolution of the stress state around subducting plate boundaries.…”
Section: Introductionmentioning
confidence: 99%